2010
DOI: 10.1016/j.wear.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Flash temperature measurement during dry friction process at high sliding speed

Abstract: An experimental method is presented in this paper to measure flash temperatures of sliding surfaces. High sliding velocities are reached by using a ballistic setup equipped with a high speed camera. The temperature field on the friction surface was recorded during the process. Tests were conducted under dry sliding conditions by using an identical material for the rubbing bodies, which are of middle hard steel (C22). Experiments showed that the temperature distribution generated by frictional heating is made u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…22 The isother- mal oxidation curves of 3D needle-punched C/C-SiC composites with Si-Mo coating in air at 1000°C are shown in Fig. 5.…”
Section: Microstructure and Propertiesmentioning
confidence: 99%
“…22 The isother- mal oxidation curves of 3D needle-punched C/C-SiC composites with Si-Mo coating in air at 1000°C are shown in Fig. 5.…”
Section: Microstructure and Propertiesmentioning
confidence: 99%
“…This device has already established the presence of localized flash temperatures higher than 800 C for steel on steel friction, due to interactions between the two sample asperities. [7] The goal of Raman spectroscopy is then to confirm and characterize more precisely the distribution of those areas as well as validate the reached temperature values thanks to a postmortem observation.…”
Section: Friction Devicementioning
confidence: 99%
“…Consequently, the opportunity to rebuild the temperature field on the outermost surface is a key factor for determining the friction factor value. A recent experimental study of Sutter and Ranc [7] showed that friction between two samples of medium-low carbon steel at 34 m/s can induce flash temperatures over 1100 C. Bogdanovich and Tkachouk [8] showed that temperature reached between two asperities can attain the melting point of the softer material. They were pioneered by Block [9] who has first highlighted the flash temperature concept.…”
Section: Introductionmentioning
confidence: 99%
“…Inaccuracy in measurement also occurs in the case when the heat transfer coefficient of the sample operating in oil is measured. The other group of authors [17,18,19,20] tries to solve the problem of measurement inaccuracy by contactless measurement in the close vicinity of the heat source. The benefit of this method is that it can be conducted very quickly, but on the other hand, its disadvantage are the problems related to the influence of environmental and operating conditions, inaccessibility of the area and the object to be measured, and differences between the response signals of two dissimilar materials.…”
Section: Introductionmentioning
confidence: 99%